2016
DOI: 10.3390/toxins8110339
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-2-pyridone-5-carboxamide (2PY)—Major Metabolite of Nicotinamide: An Update on an Old Uremic Toxin

Abstract: N-methyl-2-pyridone-5-carboxamide (2PY, a major metabolite of nicotinamide, NAM) was recently identified as a uremic toxin. Recent interventional trials using NAM to treat high levels of phosphorus in end-stage renal disease have highlighted new potential uremic toxicities of 2PY. In the context of uremia, the accumulation of 2PY could be harmful—perhaps by inhibiting poly (ADP-ribose) polymerase-1 activity. Here, we review recently published data on 2PY’s metabolism and toxicological profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…We recently used a sensitive, specific liquid chromatography–tandem mass spectrometry (LC-MS/MS) method to assay 2PY concentrations in healthy volunteers ( n = 65) and in patients with CKD (60 non-dialysed and 80 on haemodialysis). Our data confirmed that 2PY levels rise progressively with the CKD stage; the highest concentration was observed in patients on haemodialysis and greatly exceeded the value determined for healthy subjects [ 24 ]. This finding is important in view of the renewed interest in nicotinamide for the treatment of hyperphosphataemia in patients with advanced CKD [ 25 ].…”
Section: N -Methyl-2-pyridone-5-carboxamide: a Comeback By Asupporting
confidence: 85%
“…We recently used a sensitive, specific liquid chromatography–tandem mass spectrometry (LC-MS/MS) method to assay 2PY concentrations in healthy volunteers ( n = 65) and in patients with CKD (60 non-dialysed and 80 on haemodialysis). Our data confirmed that 2PY levels rise progressively with the CKD stage; the highest concentration was observed in patients on haemodialysis and greatly exceeded the value determined for healthy subjects [ 24 ]. This finding is important in view of the renewed interest in nicotinamide for the treatment of hyperphosphataemia in patients with advanced CKD [ 25 ].…”
Section: N -Methyl-2-pyridone-5-carboxamide: a Comeback By Asupporting
confidence: 85%
“…However, at high concentrations NAM and MeNAM can have a toxic effect on neurons, as shown in Parkinson's and Huntington's disease models [39][40][41] . Similarly, NAM has been shown to be effective for management of hyperphosphatemia in patients with renal disease 42 ; however, it is also suggested to be a uremic toxin contributing to thrombocytopenia 43,44 . Whilst there have been studies showing NR safely elevates NAD + in human blood 16,17,45 it is important to consider that creating a state of NAD + excess and increasing clearance of NAM and MeNAM could potentially have unintended effects in the CNS and for kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…2Py has previously been classified as a uremic retention product by the European Uremic Toxin Working Group [32,33], though specific mechanisms of its renal clearance have yet not been characterized. Whereas plasma concentrations of 2Py are reported to increase progressively with chronic kidney disease stages [34], those of N 1 -MN are suggested to be less sensitive to kidney function because of the contribution of AOX1 to N 1 -MN clearance [13,14]. In view of this, we can speculate upon slower excretion of N 1 -MN, hence prolonged exposure to 2Py-forming AOX1 that is related to kidney function, rather than retention of 2Py primarily.…”
Section: Discussionmentioning
confidence: 88%